Benefits of swaying while standing to higher selective attention in goal-directed visual tasks - Hua, Anke; Guillaume, Mélen; Rodrigues, Sergio T. [UNESP]; Barbieri, Fabio A. [UNESP]; Bonnet, Cédrick T. (Elsevier, 2025)
Background and aim: Sit-stand desks allow individuals to work in either sitting or standing position. While previous studies have reported better performance on the attention network test (ANT) while standing compared to sitting, the relationship between body sway induced by these positions and ANT performance remains unclear. In this study, we aimed to test and expect benefits of body sway (in terms of magnitude and complexity) and improvements in ANT performance when standing (e.g. shorter reaction time) but not when sitting. Methods: Seventeen young adults (mean age = 21) performed reading tasks, questionnaires and ANTs sequentially in both standing and sitting positions. We measured body kinematics from the head, upper back and lower back during the study. We calculated the linear (i.e., velocity) and nonlinear (i.e., fractal dimension) variables of body sway, reaction times and alerting scores from the ANT. Our results showed that when standing, the complexity of sway was significantly negatively correlated with ANT reaction times (shorter reaction time indicating better performance) and significantly positively correlated with the scores of alerting from ANT. Hence, consistent with our expectation, ANT performance was higher when standing potentially because participants adjusted their sway. In contrast, while sitting, there was no significant correlation between body sway and ANT performance. Overall, the complexity of body sway in the standing position may increase alertness levels, potentially leading to better visual task performance. Practically, these findings suggest that working occasionally in the standing position is beneficial, as dynamic postural sway can enhance visual task performance.
Keywords: Attention network test; Fractal dimension; Postural control; Standing vs. sitting; Young adults